Pengembangan Sistem Pemantauan Pasien Jarak Jauh Berbasis IoT Untuk Deteksi Dini Serangan Jantung - Yonida, Sayoga Dwi; Suryani Faradisa, Irmalia; Limpraptono, F Yudi (SinarFe7, 2025)
The heart is a vital organ that pumps blood throughout the body. Disorders such as bradycardia or tachycardia often occur without obvious symptoms, so a heart monitoring system capable of detecting these conditions early is needed. This study aims to design an Internet of Things (IoT)-based heart monitoring system using AD8232 and MAX30100 sensors with an ESP32 microcontroller. The system displays real-time data via a 16x2 LCD and a local web server. The research method used is experimental, including hardware and software design as well as testing under various heart rate conditions. The system is designed to read electrocardiogram (ECG) signals, calculate heart rate (BPM), measure oxygen saturation (SpO₂), and classify heart conditions. Test results show that the system can read ECG signals, calculate BPM based on R-peak detection, and classify conditions into NORMAL, BRADYCARDIA, or TACHYCARDIA categories. The five-point moving average digital filter method proved effective in reducing noise in ECG signals. Data is displayed synchronously via LCD and web pages using the Server-Sent Events (SSE) method. An additional switch also successfully displays the local IP address. This system is considered efficient, portable, and usable by the general public, especially in areas with limited access to medical services.